1968
DOI: 10.1210/endo-82-5-959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Injection of an Estrogen Antagonist on the Estrous Cycle of the Rat1

Abstract: As previously demonstrated, ovariectomy of rats with 4-or 5-day estrous cycles at 1600 hr on the day before proestrus but not at 1000 hr on the morning of proestrus blocks vaginal cornification and mating. When performed at 1000 hr on the day prior to proestrus, ovariectomy also blocks the proestrous uterine weight increase and the drop in pituitary LH. A single injection of MER-25, a nonsteroidal estrogen antagonist, was given at specific times in the estrous cycle to investigate whether the responses blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…Although basal estradiol levels were observed on metestrus and diestrus days, the expression of both receptors was lower on metestrus and increased gradually until reaching its maximum level at 16 h of diestrus afternoon. Increased levels of estradiol are required to activate the LH surge on proestrus afternoon since administration of estradiol inhibitors (Shirley et al 1968) and estradiol antiserum (Neill et al 1971) on diestrus blocks the proestrus LH surge. In this regard, this increase in the number of ER-ir cells in LC may be a way to prepare this nucleus to respond to the increase of estradiol levels which starts in the late evening of diestrus (Smith et al 1975) in order to activate the LH surge on proestrus afternoon, which was observed at 16 h in our study.…”
Section: Locus Coeruleusmentioning
confidence: 99%
“…Although basal estradiol levels were observed on metestrus and diestrus days, the expression of both receptors was lower on metestrus and increased gradually until reaching its maximum level at 16 h of diestrus afternoon. Increased levels of estradiol are required to activate the LH surge on proestrus afternoon since administration of estradiol inhibitors (Shirley et al 1968) and estradiol antiserum (Neill et al 1971) on diestrus blocks the proestrus LH surge. In this regard, this increase in the number of ER-ir cells in LC may be a way to prepare this nucleus to respond to the increase of estradiol levels which starts in the late evening of diestrus (Smith et al 1975) in order to activate the LH surge on proestrus afternoon, which was observed at 16 h in our study.…”
Section: Locus Coeruleusmentioning
confidence: 99%
“…In the immature female rat, induction of an LH surge by exogenous steroid administration induces Fos expression in LHRH neurons (20). The dependence of the natural LH surge on gonadal steroids (21) strongly suggests that LHRH neurons would similarly express Fos at the time of the LH surge on the day of proestrus. Thus, in the present study, we used Fos expression to identify the neurons activated during the preovulatory LH surge as a means of defining the population of LHRH neurons that stimulate the LH surge.…”
mentioning
confidence: 99%
“…The GnRH signal elicited high-amplitude surges of LH only in the presence of a peak estradiol concentration. Our findings are consistent with the conclusion that two actions are required for a rise in estradiol to elicit a full-amplitude surge of LH in the ewe: an action on the brain to evoke a sudden increase in GnRH release and an action on the pituitary to maximize its response to GnRH.Although it has long been recognized that a rise in circu lating estradiol induces the preovulatory discharge of lu teinizing hormone (LH) in spontaneously ovulating mam mals, the sites and mechanisms through which estradiol acts have been the subject of considerable debate [10,16,17,29,47,51]. On the one hand, increased gonadotropin-releasing hormone (GnRH) secretion during the LH surge has been suggested in the monkey [32,36], rat [43] and sheep [5,6,45], and certainly would seem an important mode of action for estradiol.…”
mentioning
confidence: 99%